ANALISIS PERAMALAN PERMINTAAN PRODUKSI SEPATU DI PT. XYZ DENGAN METODE STRAIGHT LINE - Waliyani, Resti; Alicia, Tresa; Ihsan, Tiaradia (CV SWA Anugerah, 2025)
The footwear sector in Indonesia, being an essential part of the economy, encounters challenges like demand fluctuations, evolving fashion trends, and fierce competition. XYZ, a shoe manufacturer based in Cibaduyut, Bandung, emphasizes quality and innovation, crafting approximately 50,000 pairs of footwear each month. The manufacturing process involves cutting, stitching, assembling, and finishing, necessitating specialized expertise. The organization is dedicated to adopting contemporary and sustainable technologies, such as waste management and utilizing environmentally friendly materials. Precise production planning is essential to guarantee that product availability meets market demand, helping to prevent the dangers of excessive inventory or shortages. The straight-line approach, while uncomplicated, is useful for predicting production patterns using past data. This research examines the use of this technique in predicting shoe production at a firm, with the goal of obtaining a precise insight into the necessary production quantity for the future. The findings of this study are anticipated to aid management in decision-making related to production capacity, inventory control, and cost-effectiveness, allowing the company to adapt to market needs and reduce risks and losses linked to production.